Corporate Social Responsibility for Economic Recovery Post-Pandemic: A Lesson from Bank Syariah Indonesia - Aminudin Ma'ruf; Rahayu Puji Lestari; Azhar Alam (At-Taradhi Jurnal Studi Ekonomi, 2023)
This study aims to determine the implementation of BSI's CSR programs to support economic recovery post-pandemic, and identify the supporting and inhibiting factors in implementing its programs. The method used for this research is a qualitative method that presents actual data according to conditions in the field by direct interviews with associated parties. The study results show that BSI has set a strategy to optimize its CSR program, one of which is by focusing on empowering MSMEs. In Indonesia, MSMEs are considered the main factor for accelerating economic recovery. In its implementation, CSR at BSI indeed encounters supporting factors as well as inhibiting factors. The supporting factor is the existence of an ecosystem in implementing CSR programs, to which many parties contribute. The obstacles encountered were the lack of public understanding and education of CSR programs.